2004
DOI: 10.1080/usp.28.1.49.52
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Extrarenal Rhabdoid Tumor with a Unique Long-Term Survival

Abstract: Rhabdoid tumors of kidney and extrarenal rhabdoid tumors are identified by a round-epithelioid cell morphology and a bland immunophenotype, but a distinctive ultrastructure dominated by paranuclear whorls of intermediate filaments, most usually of vimentin. These tumors are also known to be highly aggressive malignancies, which, typically, bear a poor prognosis, frequently measured in months following initial presentation. The authors record the case a soft-tissue rhabdoid tumor in a 12-year-old boy with a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…2,3 Although extra-renal rhabdoid tumors (ERTs) arising in the livers of pediatric patients (hepatic rhabdoid tumors; HRTs) have a poor outcome, 4 there have been some recent reports of exceptional ERTs affecting young adults or showing outcomes that were not necessarily poor, but with pathological features that varied among the cases. [3][4][5][6] Here we present a case of rhabdoidmimicking IC and discuss the differences between this case and conventional ERTs on the basis of immunohistochemical and ultrastructural observations.…”
Section: A Rhabdoid-mimicking Intrahepatic Cholangiocarcinomamentioning
confidence: 92%
See 2 more Smart Citations
“…2,3 Although extra-renal rhabdoid tumors (ERTs) arising in the livers of pediatric patients (hepatic rhabdoid tumors; HRTs) have a poor outcome, 4 there have been some recent reports of exceptional ERTs affecting young adults or showing outcomes that were not necessarily poor, but with pathological features that varied among the cases. [3][4][5][6] Here we present a case of rhabdoidmimicking IC and discuss the differences between this case and conventional ERTs on the basis of immunohistochemical and ultrastructural observations.…”
Section: A Rhabdoid-mimicking Intrahepatic Cholangiocarcinomamentioning
confidence: 92%
“…5 Ultrastructurally, RT cells show coexpresson of vimentin and low-molecularweight cytokeratin with characteristic whorls of intermediate filaments. 7 Although many ERTs with exceptional clinical features have been reported, i.e., those affecting adults 4 and not necessarily showing a poor outcome, 6 they may not show the same immunohistochemical phenotype, or have not been studied ultrastructurally. [3][4][5][6] The present case simulated ERT morphologically but was negative for vimentin with looser aggregates of intermediate filaments, and had a favorable outcome.…”
Section: A Rhabdoid-mimicking Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…We came across to 32 patients with extrarenal MRT cases under 3 years old and only few of those were congenital 1–3,5–7. The treatment of disseminated MRT is very difficult 3–5,8,9. Kodet et al 3 reported that almost all patients less than 1 year of age died within months despite multi‐agent chemotherapy in all patients (n:11) plus radiation therapy in three patients.…”
Section: To the Editormentioning
confidence: 99%
“…Опухоль встречается во всех возрастных категориях от 0 до 18 лет с медианой 8-9 лет [1,16]. Описаны случаи врожденных ЭРО [1,17] и редкие случаи возникновения опухолей у взрослых пациентов [18][19][20][21]. Мальчики болеют незначительно чаще девочек в соотношении 1,5:1 с частотой встречаемости 15 случаев в год у детей в возрасте до 15 лет в Северной Америке, 6 случаев в год в Германии [1,8,9].…”
unclassified